In Bangladesh, A Techno-Economic Evaluation of Rice Straw Based Power Generation (AIUB Journal of Science and Engineering (AJSE), 2024)
The Availability of sufficient electrical energy is essential for a nation’s economic growth to be steady. Bangladesh should, therefore, have enough electricity infrastructure to maintain its economic growth. Several kinds of agricultural waste are available in Bangladesh as an agricultural country. Therefore, Bangladesh may generate energy (such as electricity) from this enormous agricultural waste. One of the potential agricultural wastes for use as a source of energy is rice straw, but only if it is properly and methodically processed. This research investigates the technical potential of using filtered rice straw to produce energy in Bangladesh. Environmental risks are posed by the estimated 4 million tonnes annual burn of rice straw in an open field. Rice straws can produce a net annual electricity output of 217.21 GWh, corresponding to an input of 8640 tonnes of rice straw, according to simulation and full-scale experiments. But our country’s available rice straw is almost 119.3 million tonnes/year. Notice that we used 17-tonne rice straw in the aspen simulator. The plant can reduce CO2 emission of 0.03%. Total cost is $4,082,005 per year, and the per unit cost is $0.019. This thesis work aims to present a concept for producing electricity in Bangladesh’s rural areas using rice straw. Small and medium-sized power plants based on rice straw are very helpful for producing and distributing electricity in rural areas. A comprehensive process model for biomass gasification in a twin-fire fixed bed gasifier is developed using the ASPEN PLUS simulator. The chemical process industries primarily use the process modeling tool Aspen Plus for process monitoring, optimization, and conceptual design. This simple course on the Aspen Plus Simulation engine will teach you how to model the most common chemical plant unit operations.